Complementarity of dockless mircomobility and rail transit. (July 2022) - Tyndall, Justin
Abstract: Shared micromobility services have undergone rapid growth in cities throughout the world, including expansions in bike sharing and e-scooter sharing services. Shared micromobility provides a potential complement to public transit by accommodating first and last-mile trips. I analyze detailed data on shared, dockless bikes and e-scooters from Seattle, Washington. I find micromobility vehicles cluster near Seattle's rail transit stations. During the study period, Seattle expanded its rail system into a new section of the city. I use the system expansion as a natural experiment to provide evidence of complementarity between shared micromobility and public transit. Using a differencein-difference strategy I find that, after a new light rail station opened, the flow of new micromobility vehicles increased significantly within a 5 min walking radius of the station. I provide causal evidence that local rail transit increases the use of dockless micromobility vehicles.